Application of the Diabetes Self-Care Activities Questionnaire (SDSCA) during the COVID-19 pandemic (Research, Society and Development, 2022)
Diabetes Mellitus (DM) can be understood as a group of metabolic diseases, characterized by increased blood glucose levels due to a disturbance in the secretion or action of insulin. According to some studies DM is a prevalent factor for COVID-19 (Coronavirus Disease 2019). Type 2 Diabetes Mellitus (DM2) is one of the most challenging health problems of the 21st century. Faced with this scenario the aim of this work is to apply the Diabetes Self-Care Activity Questionnaire (SDSCA) in volunteers with DM2 during the COVID-19 pandemic. The study was conducted in the municipality of Poço Fundo/MG and the volunteers were invited in the Family Health Program (PSF) units of the Unified Health System (SUS). The SDSCA has 15 items for assessment of self-care with DM, distributed in seven dimensions: "general diet", "specific diet", "physical activity", "blood glucose monitoring", "foot care", and "medication use". They also include three other items for the evaluation of smoking. Spearman's correlation and descriptive analysis were performed for data interpretation. We conclude that the SDSCA is a reliable instrument to measure self-care adherence in type 2 diabetic volunteers. Through this questionnaire we can observe that the volunteers knew some important cares and we believe that from then on they can make them part of their routine.